Design of Shell and Tube Heat Exchanger for Magnetite (Fe3o4) Particle Production Process - Agung Slamet Nugraha; Asep Bayu Dani Nandiyanto (Indonesian Journal of Multidiciplinary Research, 2023)
Shell and tube heat exchangers are one of the most widely used types of heat exchangers in industry. The low cost of manufacture and use is one of the reasons this heat exchanger is widely used. The purpose of this research is to design a shell and tube heat exchanger (two-pass) type for application in the production of magnetite particles on an industrial scale. To design a heat exchanger, the method used is mathematical calculations using more than 20 equations that are used which are derived based on the influence of dimensional and fluid specifications. In the production of magnetite particles, two heat exchangers are used, namely the reaction process and the crystallization process. The results of this study indicate the effectiveness of the two heat exchangers designed to have a high enough value and exceed 70%. This high effectiveness value indicates that both heat exchangers have good performance. Therefore, this design has the potential to be applied to the magnetite particle synthesis process on an industrial scale.